INFORMATION SYSTEM DESIGN IN THE YAMAHA MUSIC SCHOOL - Soleh Prabowo; Eko Hadiyanto, SSi, MMSI (Jurnal Sistem Informasi, 2000)
The design of information systems was written because this now need the speed and accuracy needed by someone to assist their daily work. In the writing of this, the authors try to design a system to manage the company to facilitate the routine work performed by employees, both in terms of administrasian, education, until the preparation of reports to the CEO.  In this system, also outlined the differences between the old system with a new system so it can be seen how quickly the new system.